ダイ15ジ ナンキョク チイキ カンソクタイ エットウタイ ホウコク 1974 1975 - 村越, 望; ムラコシ, ノゾミ; MURAKOSHI, Nozomi (国立極地研究所, 1976)
P(論文) The 15th wintering party consisting of thirty members was in charge of research activities at Syowa Station for the period from February 1974 to January 1975. Objects of research were aurora, geomagnetism, ionosphere, meteorology, oceanography, seismology, glaciology, geomorphology, geology, biology, geochemistry and medical science. The inland traverse party made a 80-day trip from October 1974 to January 1975 in Yamato Mountains area. The object was geological survey and about 650 meteorites were collected. Other inland party made a 84-day trip from October 1974 to January 1975 in southern part of the Mizuho Plateau and in the Sandercock Nunataks. The main objects were traverse glaciology and meteorology. Mizuho Camp was expanded with new observation hut, boring site and snow tunnel. Three or six members stayed at camp for 2 months from December 1974 to February 1975, and performed coredrilling of ice down to the 150m. The single engine monoplane, Cessna 185 used by JARE-15 as first wintering and engaged in aeromagnetic survey, reconnaissance and transportation. Total flight time was about 80 hours in 1974. departmental bulletin paper